Learning Processes as Key for Success in Workplace Health Promotion Interventions in Health Care - Eriksson, Andrea; Dellve, Lotta (Frontiers in Public Health, 2020)
There is limited previous research on how learning processes contribute to the outcomes of workplace health promotion (WHP) leadership interventions. The aim of this study was to identify the outcomes of a system-based WPH education program for managers and investigated what impact the intervention program had on health-oriented leadership, improvement work, and employee well-being, as well as what factors (i.e., how manager's active work following the intervention and organizational learning climate) contributed to these outcomes. A mixed-methods approach was applied, including qualitative interviews with 23 managers and process leaders, as well as questionnaires to employees and managers representing 17 public health care units in Sweden. The results showed that health-oriented leadership, improvement work, work satisfaction, and vitality increased at workplaces that worked actively to implement WHP following the program. Working actively with WHP and health-oriented leadership was of central importance for success and was a covariate with improved social learning climate, improved developmental leadership, and increased degree of improvement work. All included factors of learning during the intervention were associated with improved job satisfaction, while the increase in vitality seemed unrelated to program implementation. In conclusion, successful outcomes of WHP interventions interact with dimensions of organizational learning climate in the workplace.